The role of brand awareness, e-WOM, and perceived quality on purchase intention of Viva cosmetics in Medan - Jeybi, Jeybi; Alfonsius, Alfonsius (Institute of Computer Science (IOCS), 2024)
Viva Cosmetics is one of the oldest cosmetic brands known for their affordable prices and formulations that are suitable for tropical environments. As the beauty industry keeps evolving, there has been a noticeable decrease in the purchase intention of Viva Cosmetics’ products which can be predicted through brand awareness, e-WOM, and perceived quality. This research intends to examine the role of these variables on the purchase intention of Viva Cosmetics among consumers in Medan. Descriptive quantitative and causal method are implemented in this research. Sample is determined using non-probability sampling (accidental sampling) with a total of 97 respondents. Multiple linear regression is used to analyze the data in this research. Results show that brand awareness, e-WOM, and perceived quality partially and significantly influence the purchase intention of Viva Cosmetics in Medan. Brand awareness, e-WOM, and perceived quality also influence the purchase intention simultaneously